Anti-inflammatory effects of anisalcohol on lipopolysaccharide-stimulated BV2 microglia via selective modulation of microglia polarization and down-regulation of NF-κB p65 and JNK activation. (March 2018) - Xiang, Bin; Xiao, Chun; Shen, Ting; Li, Xiufang
Highlights: Our data demonstrate that PMBA can selectively modulate microglia polarization. PMBA can inhibit the transformation of microglia into M1 phenotype and promote its transformation into M2 phenotype. PMBA can attenuate the production of inflammatory mediators and cytokines. The modulation of microglia M1/M2 polarization of PMBA may be related to multiple mechanisms, mainly inhibiting the activation of NF-κB and MAPK. These findings suggest that PMBA may have the potential to treat cerebral ischemic events. Abstract: Inflammation plays a pivotal role in the pathogenesis of ischemic stroke. The inhibition of inflammation appears to be a potential therapeutic strategy for neuro-inflammatory injury after ischemic stroke. In response to cerebral ischemia, resident microglia and infiltrated macrophages from the damaged blood–brain barrier are activated. Microglia activation appears to be a double-edged sword. Activated microglia migrate to the damaged neuron, change their phenotype to M1 or M2, and become involved in nerve damage and repair. M1 phenotype microglia express multiple inflammatory factors to exacerbate secondary brain injury, while those of M2 phenotype release anti-inflammatory factors to promote brain recovery after ischemic stroke. Therefore, the regulation of microglia M1/M2 phenotype after ischemic stroke is crucial for brain repair. The present study aimed to investigate the anti-inflammatory effect of anisalcohol ( p -methoxybenzyl alcohol, PMBA), a phenolic compound from Gastrodia elata Blume, which has been shown to reduce cerebral ischemic injury in rodents. However, no studies have specifically addressed whether PMBA can selectively modulate microglia polarization. In this study, lipopolysaccharide-stimulated BV2 microglia were used to assess the anti-inflammatory effect of PMBA. The results revealed that PMBA significantly reduced the lipopolysaccharide-induced production of tumour necrosis factor α, prostaglandin E2, and nitric oxide, without causing cell toxicity. In addition, it increased anti-inflammatory interleukin-10 and transforming growth factor-β. Phenotypic analysis of LPS-stimulated BV2 microglia showed that PMBA significantly down-regulated the expression of the M1 marker CD16/32 and up-regulated that of the M2 marker CD206. Moreover, PMBA suppressed NF-κB activation and inhibited the phosphorylation of JNK in LPS-stimulated BV2 microglia. Collectively, our data demonstrate that PMBA can inhibit M1 transformation and promote M2 transformation of microglia, thus attenuating the production of inflammatory mediators and cytokines. The modulation of microglia M1/M2 polarization may involve multiple mechanisms, mainly, the inhibition of NF-κB and MAPK activation. These findings suggest that PMBA acts as an anti-inflammatory factor and is a possible therapeutic candidate for diseases such as ischemic stroke, where inflammation is a central hallmark.